An Error Analysis Made by the English Department Students in Translating Tourism Brochure - Walanda, Anisa Erda; Ardi, Havid (Journal of English Language Teaching, 2024)
This study aims at finding out the types of errors made by the English Department students of Universitas Negeri Padang in translating tourism brochure from Bahasa Indonesia into English. This study used a descriptive qualitative method. The data were the translation of tourism brochures of the  entitled “Lembah Harau, Indahnya Minangkabau” and “Destinasi Wisata Alam yang Masih Alami di Sumatera Barat” done by English Department students of Universitas Negeri Padang who have taken Indonesia English Translation Subject. The data were collected using a test and were analyzed using the error analysis. The results of the study indicate that there are four types of errors  which  error  of devition of  meaning  is  the most error frequently   committed   by   the   students   in   their translation   with   the   frequency   of   180 times   (63,15%). Omission of meaning (26.66%) is the second, while the error of addition and the error of invention  of  meaning  are  the  least  error  found  in  the students’ translation.